DOI: 10.11606/d.58.2019.tde-19072019-075251
|View full text |Cite
|
Sign up to set email alerts
|

Reabsorção dentária nos ameloblastomas: um sinal importante para o diagnóstico diferencial

Abstract: Aos meus pais, Braz e Zezé. Vocês são minha inspiração. Não tem nada que eu faça que não seja pensando em vocês. Espero um dia conseguir ser metade do que vocês são pessoal e profissionalmente, e dar a vocês o mesmo orgulho que eu tenho de tê-los como pais. Amo vocês!! À minha irmã, Bruna. Você que esteve comigo sempre, em todos os meus melhores e piores momentos. Obrigada por ser um exemplo, eu te admiro imensamente. Á minha sobrinha Ana Laura. Você é luz. Vida. Amor.Ao meu tio César. Você que sem perceber me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…As a contribution to understanding this phenomenon, this study explores this question and discusses a possible mechanism described in the literature 5 .…”
Section: The Four Most Frequent Cysts Associated With Vital Teeth: Whmentioning
confidence: 99%
See 1 more Smart Citation
“…As a contribution to understanding this phenomenon, this study explores this question and discusses a possible mechanism described in the literature 5 .…”
Section: The Four Most Frequent Cysts Associated With Vital Teeth: Whmentioning
confidence: 99%
“…Martins 5 studied 50 cases of ameloblastoma and found that, if the roots associated with the cystic-like tumor are resorbed, the chance of a diagnosis of ameloblastoma is so high that resorption may be considered a pathognomonic sign (Figs 1 to 5). If there is no associated root resorption, it is very probably an odontogenic keratocyst or another lesion.…”
Section: Why Do Ameloblastomas Involving Teeth Have Knife-edge Root Rmentioning
confidence: 99%